2013
DOI: 10.1111/infa.12037
|View full text |Cite
|
Sign up to set email alerts
|

Infants' Perception of Intonation: Is It a Statement or a Question?

Abstract: The ability to distinguish phonetic variations in speech that are relevant to meaning is essential for infants' language development. Previous studies into the acquisition of prosodic categories have focused on lexical stress, lexical pitch accent, or lexical tone. However, very little is known about the developmental course of infants' perception of linguistic intonation. In this study, we investigate infants' perception of the correlates of the statement/yes-no question contrast in a language that marks this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 57 publications
(93 reference statements)
2
60
1
7
Order By: Relevance
“…The first is that, like many distributional learning mechanisms (though see Frank, Goldwater & Keller, 2013 Given the obvious prosodic, pragmatic and structural differences between declaratives and questions, this feature of the model might be regarded as somewhat implausible, particularly in view of recent evidence that even very young children can distinguish between declaratives and questions in the input (Seidl, Hollich & Jusczyk, 2003;Homae, Watanabe, Nakano, Asakawa & Taga, 2006;Soderstrom, Ko & Nevzorova, 2011, Geffen & Mintz, 2012Frota, Butler & Vigário, 2014). For example, Geffen and Mintz (2015) show that by 12 months children can distinguish between declaratives and polar interrogatives even in the absence of prosodic cues, and argue that although infants initially use phonological information to distinguish between sentence types, they have already begun to learn generalisations about the corresponding word-order patterns before the onset of multi-word speech.…”
Section: Limitations Of the Current Version Of Mosaicmentioning
confidence: 99%
“…The first is that, like many distributional learning mechanisms (though see Frank, Goldwater & Keller, 2013 Given the obvious prosodic, pragmatic and structural differences between declaratives and questions, this feature of the model might be regarded as somewhat implausible, particularly in view of recent evidence that even very young children can distinguish between declaratives and questions in the input (Seidl, Hollich & Jusczyk, 2003;Homae, Watanabe, Nakano, Asakawa & Taga, 2006;Soderstrom, Ko & Nevzorova, 2011, Geffen & Mintz, 2012Frota, Butler & Vigário, 2014). For example, Geffen and Mintz (2015) show that by 12 months children can distinguish between declaratives and polar interrogatives even in the absence of prosodic cues, and argue that although infants initially use phonological information to distinguish between sentence types, they have already begun to learn generalisations about the corresponding word-order patterns before the onset of multi-word speech.…”
Section: Limitations Of the Current Version Of Mosaicmentioning
confidence: 99%
“…Insert Table 1 here _________________________________________ 2 One-word utterances were used since this is the most common prosodic domain for a melody in EP infant-directed speech (Frota, Butler & Vigário, 2014).…”
Section: _________________________________________mentioning
confidence: 99%
“…In addition, the intonation used within each sentence type in their stimuli was very variable (e.g., declarative sentences ending with either flat, falling or bell shaped contours), which may have affected infants' perception of the contours. Frota, Butler & Vigário (2014) utilised single prosodic word utterances differing in prosodic cues related to the statement/yes-no question contrast in European Portuguese, a language that marks this contrast by prosodic cues only (in EP, unlike in English, there is no inversion in yes-no questions -Mateus, Brito, Duarte, Faria, Frota, Matos, Oliveira, Vigário, & Villalva, 2003). They found that both 5-6 and 8-9 month-old European Portuguese learning infants were able to discriminate the sentence type prosodic contrast despite segmental variability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations